New Plants for Florida: Tomato - Jay Scott; Richard L. Jones; Mary Duryea; Berry J. Treat (EDIS)
The program at FAES has provided improvements that have allowed tomato to be grown successfully in Florida and it has had a significant impact on production worldwide. Major achievements in the breeding program have been the development of disease-resistant varieties and the improvement of fruit quality. This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.